COMPARING MEDICINAL PLANTS USE FOR TRADITIONAL AND MODERN HERBAL MEDICINE IN LONG NAH VILLAGE OF EAST KALIMANTAN - Suharjito, D -; Darusman, L.K -; Darusman, D. -; Suwarno, E. - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2014)
The purpose of this research is to describe theequivalence of local knowledge and scientific knowledgeor western knowledge in terms of medicinal plantusage for traditional medicine (TM) or ethnomedicineand modern herbal medicine or jamu (MM), and therecognition of both. This descriptive-comparative researchwas accomplished using the case study method.The research used participant observation and semistructuredinterview techniques to collect data andinformation from traditional healers, communityleaders, and villagers. The research results show thaton the one hand, local people particularly traditionalhealers (dukun) have developed knowledge of medicinalplants and TM compounds. This knowledgehas been based on the existence of illnesses in thecommunity and availability of medicinal plants in theirenvironment. On the other hand, rural communityhas known, acknowledged, and consumed MM as acomplement to TM produced by traditional healers(dukun). Comparison of medicinal plants used for TMand MM is not appropriate to prove the equivalenceof local knowledge and scientific knowledge, becausedifferent plant species mayhave the same efficacy. Onthe other hand, different local communities may usedifferent plants with similar efficacy for TM. Likewise,different MM industries may use different plants forMM to have the same efficacy.Key words: Local knowledge, ethnomedicine, medicinalplants, NTFPs, East Kalimantan Indonesia